KELENGKAPAN INFORMASI DAN KETEPATAN KODE DIAGNOSA CEDERA DAN PENYEBAB LUAR PADA KASUS KECELAKAAN LALU LINTAS DI TINJAU DARI BEBERAPA LITERATUR - Retno Suryaningsih; Rani Fauziah (MEDICORDHIF Jurnal Rekam Medis, 2022)
KELENGKAPAN INFORMASI DAN KETEPATAN KODE DIAGNOSACEDERA DAN PENYEBAB LUAR PADA KASUS KECELAKAANLALU LINTAS DI TINJAU DARI BEBERAPA LITERATURRani1 ; Retno.S212APIKES Bhumi Husadaretno.suryaningsih.sucipto@gmail.com2ABSTRACTInjury cases must be accompanied by an external cause of injury. So that the accuracy of the injury code and theexternal cause is correct, the ER doctors and nurses record information on the patient's condition, and the codersets the code. This review aims to analyze the completeness of the information and the accuracy of the injurydiagnosis code and external causes in the case of traffic accidents based on ICD-10, and to find out the causes ofincomplete and inaccurate injury codes and external causes. The method used in this study is a literature reviewand analytical descriptive. The results of the research on the five previous journals found that the completenessof the writing of external causes was the best percentage of the Koja Regional General Hospital 87.5% with theworst percentage of the Regional General Hospital Dr. Chasbullah Abdul Majid Bekasi City 52.6%. While theaccuracy of the injury code is the best percentage of Fatmawati Central General Hospital 100% with the worstpercentage of the Indonesian Christian University General Hospital 12%, and the accuracy of the external causecode is the best percentage of Gatot Subroto Army Central Hospital 73.9% with the worst percentage of RegionalGeneral Hospital Koja 0%. Factors that cause incomplete and inaccurate injury codes and external causes areMan, Method, Material, Machine, and Money. The injury code will be said to be correct if the writing of the injuryand external cause is complete and correct according to ICD-10. Completeness of information and accuracy ofinjury codes and external causes in cases of traffic accidents is required by the Hospital and the local police.